Vitamin D deficiency prevention policies in Iran: a retrospective policy analysis - Aghapour, Baharak; Kheirouri, Sorayya; Alizadeh, Mohammad; Khodayari-Zarnaq, Rahim (Frontiers in Nutrition, 2023)
Aim Iran has a higher prevalence of vitamin D deficiency (VDD) than the global level. This study aimed to assess VDD prevention policies in Iran through a policy analysis of agenda setting using the multiple streams framework (MSF). Methods Using Kingdon's MSF model, this qualitative analytical study performed a policy analysis on vitamin D-related policies in Iran. The policy documents were reviewed, and in-depth interviews were conducted with stakeholders (n = 27) using the framework analysis method. To categorize data and extract the related themes, MAXQDA version 10 was used. Results According to Kingdon's MSF theory, the problem stream included the high prevalence of VDD among Iranian infants (23.3%), adolescents (76%), and adults (59.1%). The policy stream was identified to focus on preventing programs for non-communicable diseases in the health sector. The political stream indicated that national and international support could provide a political climate for this issue. Conclusion According to our results, a window of opportunity for policymaking on VDD prevention has opened. However, there are some challenges related to the implementation of these policies. These include the dominance of a treatment-based view rather than a prevention-based approach in the health sector, economic problems, and restricted access to health services due to the outbreak of coronavirus disease 2019 (COVID-19). To strengthen and implement VDD prevention policies, the stakeholders need support from high-level policymakers.